2009
DOI: 10.1002/prot.22211
|View full text |Cite
|
Sign up to set email alerts
|

Using genetic algorithms to select most predictive protein features

Abstract: Many important characteristics of proteins such as biochemical activity and subcellular localization present a challenge to machine-learning methods: it is often difficult to encode the appropriate input features at the residue level for the purpose of making a prediction for the entire protein. The problem is usually that the biophysics of the connection between a machine-learning method's input (sequence feature) and its output (observed phenomenon to be predicted) remains unknown; in other words, we may onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…The superiority of EAs was recognized early [43]. Since then, many studies have demonstrated the advantages of EAs for feature generation in different domains [2], [27], [38], [35], [14], [29], [20], [18], [17].…”
Section: Related Ea Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The superiority of EAs was recognized early [43]. Since then, many studies have demonstrated the advantages of EAs for feature generation in different domains [2], [27], [38], [35], [14], [29], [20], [18], [17].…”
Section: Related Ea Workmentioning
confidence: 99%
“…Some of our recent work has shown significant improvements in classification accuracies when genetic algorithms (GA) replace k-mer feature enumeration techniques in predicting DNA hypersensitive and splice sites [18], [19], [17]. Work on predicting enzymatic activity in proteins additionally shows the power of EAs in feature generation [20].…”
Section: Related Ea Workmentioning
confidence: 99%
See 3 more Smart Citations